PENATAAN STRUKTUR ORGANISASI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN MINAHASA - TEWU, NEISSY; LENGKONG, FLORENCE; RARES, JOYCE JACINTA (JURNAL ADMINISTRASI PUBLIK, 2022)
The purpose of this study is to analyze the Organizational Structuring of the Minahasa Regency Population and Civil Registration Service in response to Government Regulation Number 41 of 2007 as an urgency for the Regional Government in the Population and Civil Registration Service to collaborate in tasks within the Government Organization. Descriptive qualitative research methods. The result of this research is an analysis of the organizational structure of the population service and civil registration by responding to Government Regulation Number 41 of 2007 which is analyzed using the theory of the Regional Apparatus Organization. The results obtained are that the analysis of the organizational structure of the Minahasa Regency Population and Civil Registration Office has been successfully implemented, but there are still obstacles in doing existing work, stalling for work, not maximizing work and only prioritizing one's own interests compared to work. Keywords: Regional Government Organizational Structuring